Saberes docentes e o ensino por investigação: contribuições de uma formação continuada em Mato Grosso do Sul - Garcia, Joelma dos Santos (2021)
The urgency of promoting scientific literacy to society is evident through teaching that encourages investigation as a way to solve problems, such as the proposal of teaching by investigation (TI). In this sense, the main objective of this research was to investigate the teaching knowledge, according to the theoretical framework of Maurice Tardif, related to TI, from the perspective of teachers who attended the continuing education offered by the Federal Institute of Education, Science and Technology of Mato Grosso do Sul (IFMS) in 2014 (Continuing education action for research professors). The research is qualitative and its data collection instruments were the interview conducted with two Biology teachers, a Physics teacher and a Chemistry teacher from the Mato Grosso do Sul State Education Network and with the two training coordinators continued - and the documentary analysis - training extension projects that. In addition to the aforementioned, also involved its second edition (2015) and the project and report of the Cycle of Workshops in basic education for teachers from the State and Municipal Network of Campo Grande (2016). In the analysis, assumptions of Content Analysis were used, which originated the categories of analysis. The data reveal that the training on the agenda provided a variety of knowledge, which was decisive for the two Biology teachers to implement the TI. As for disciplinary knowledge, we verify the relevance of the contribution to the epistemology of Science for understanding and applying the TI. Regarding curricular knowledge, time management was seen as one of the greatest difficulties for teachers, especially for teachers, who perform their work, investing themselves in that work. Teachers face dilemmas, interpreting and adapting the program according to their knowledge and conditions. Of the teachers interviewed, only Chemistry is not interested in TI, as he has more time in teaching, he already has certainties impregnated in the early years of his career, influencing his conduct, as it is during this period that experiential knowledge is intensely structured, in addition to difficulties linked to its context. The experiential knowledge provides the certainty, by the teachers, that students are more motivated when they choose the subject of their research. Experience also influences curricular knowledge and reveals that the science fair is an element of teaching-learning and also a motivational component. It also improves teachers in applying TI, as well as revealing positive results with students. However, more conditions that are appropriate for the development of TI in the analyzed contexts. As for training, even though there is a bias towards the broader practice in training in 2016, we still realize that it is not the center of training, differing from the guidelines of Tardif.